Δ‐Catenin regulates proliferation and apoptosis in renal cell carcinoma via promoting β‐catenin nuclear localization and activating its downstream target genes. (28th January 2020) - Ju, Lincheng; Shan, Liping; Yin, Bo; Song, Yongsheng
Abstract: δ‐Catenin is a unique member of the catenin family and is proved to be overexpressed in diverse human cancer types. However, the clinical significance and underling mechanism of δ‐catenin expression in renal cell carcinoma (RCC) remain elusive. Herein, we detected the protein expression of δ‐catenin in 28 clinical specimens of paired renal cancer tissues and normal renal tissues by Western blot analysis. δ‐Catenin expression in 58 cases of renal cell carcinoma was also examined by immunohistochemistry, and its association with clinicopathological factors was analyzed by statistical analysis. In vitro and in vivo assays were employed to further explore the biological role of δ‐catenin in RCC. The results showed that δ‐catenin was highly expressed in both clinical samples and cell lines of RCC. RCC patients with higher δ‐catenin expression had a more advanced pTNM stage and tumor stage as well as lymph nodes metastasis than those with lower expression. By regulating the nuclear translocation of β‐catenin and β‐catenin‐mediated oncogenic signals, δ‐catenin promoted proliferation and inhibited apoptosis in RCC. In vivo assay indicated δ‐catenin facilitated tumor growth in ACHN cell xenograft mouse model. Taken together, our study suggests that δ‐catenin might be considered as a novel prognostic indicator and actionable target for gene therapy in renal cell carcinoma. Abstract : By regulating the nuclear translocation of β‐catenin and β‐catenin‐mediated oncogenic signals, δ‐catenin promoted proliferation and inhibited apoptosis of renal cancer cells.